Metadados de mangás em biblioteca e sites de e-commerce - Moura, Yasmin Fattori Ventura de (Universidade Federal de São Carlos, 2025)
Japanese culture is becoming more and more popular around the globe and, along with it, manga, Japanese comic books. Two ways of obtaining these artistic manifestations are through libraries and e-commerce sites. However, in order for manga to be findable by their audience, metadata must be used to represent Japanese comics. Based on this context, the general objective of this research is to evaluate the manga metadata used on e-commerce sites and in libraries. The specific objectives were: to present Japanese comics; to carry out a literature search on general and specific metadata for manga; to analyze the metadata used on e-commerce sites and in libraries; to compare the analysis of manga images with the metadata. This is an applied study with exploratory objectives and a qualitative approach, as well as using bibliographical and documentary research. A form was used to collect and organize the data, and content analysis and the comparative method were used to analyze the results. As a result, it was possible to observe situations in which the library and the e-commerce sites shared the same metadata; situations in which this was only partial; and even cases in which everything was different. In addition, it was observed that there is some standardization adopted by both the library and the e-commerce sites, although it is also possible to notice differences, either on the same site or from one site to another. As for images, there were no situations in which they were represented in any of the information environments studied, despite the fact that illustrations are a fundamental part of manga. It can be concluded that, even if there are cases in which the two institutions handle the same types of metadata, their different representations and presentations may be linked to their institutional objectives.
Manga metadata on library and e-commerce sites
Keywords: Mangá; Metadados; Catalogação; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA